Academic Performance of Enrolled Students in the University of Lahore, Pakistan - Jawad, Sana; Naveed, Haleema; Akram, Muhammad Bilal (Quest Journal of Management and Social Sciences, 2020)
Background: This study investigates the academic performance of students, enrolled at the University of Lahore, Pakistanto different programs in Spring-2019. The study measuredthe academic performance of students using the Cumulative Grade Point Average (CGPA). The variables under consideration were academic performance(students’ percentage, CGPA, and GPA). A total number of nine hundred and fifty eight (958) students were enrolled in Spring-19 with CGPA’s in Undergraduate BS (Hons) Programs, (246) Graduate (MS/MPhil.) Programs, and (11) Postgraduate (Ph.D.) Programs. Objective: The report aims to identify the relationship between percentage of marks with undergraduates and graduates, enrolled at the University of Lahore, Pakistan to different programs in Spring-2019. Methods: Undergraduate BS (Hons), Graduate (MS/M.Phil.) and Postgraduate (PhD) students were taken as the target population for the research sample. Data were collected with the help of an array of technology support, and management. For analysis, the frequency analysis, descriptive analysis and correlation are used through the aid of Statistical Package for the Social Science (SPSS) version 23. Results: Results show that the performance of students, enrolled with a weak academic background, had poor performance in enrolled programs. On the other hand, students, enrolled with high academic background, maintained their excellent performance in the first semester of their enrolled programs. Also, we observe that the students who were enrolled with a high percentage of marks show poor and average performance in the first semester. Conclusions: We can infer from this analysis that only the students who were enrolled with a high percentage can achieve a high GPA in the semester. And likewise, students who weren’t enrolled with a good percentage of marks cannot achieve a high GPA in the first semester. Originality: This is the original work of author and not submitted for publishing in other publications.